The rice mitochondria proteome and its response during development and to the environment - Huang, Shaobai; Shingaki-Wells, Rachel N.; Taylor, Nicolas L.; Millar, Harvey (Frontiers in Plant Science, 2013)
Rice (Oryza sativa L.) is both a major crop species and the key model grass for molecular and physiological research. Mitochondria are important in rice, as in all crops, as the main source of ATP for cell maintenance and growth. However, the practical significance of understanding the function of mitochondria in rice is increased by the widespread farming practice of using hybrids to boost rice production. This relies on cytoplasmic male-sterile (CMS) lines with abortive pollen caused by dysfunctional mitochondria. We provide an overview of what is known about the mitochondrial proteome of rice seedlings. To date, more than 320 proteins have been identified in purified rice mitochondria using mass spectrometry. The insights from this work include a broad understanding of the major subunits of mitochondrial respiratory complexes and TCA cycle enzymes, carbon and nitrogen metabolism enzymes as well as details of the supporting machinery for biogenesis and the subset of stress-responsive mitochondrial proteins. Many proteins with unknown functions have also been found in rice mitochondria. Proteomic analysis has also revealed the features of rice mitochondrial protein presequences required for mitochondrial targeting, as well as cleavage site features for processing of precursors after import. Changes in the abundance of rice mitochondrial proteins in response to different stresses, especially anoxia and light, are summarized. Future research on quantitative analysis of the rice mitochondrial proteomes at the spatial and developmental level, its response to environmental stresses and recent advances in understanding of basis of rice CMS systems are highlighted.